Q. 104.3( 18 Votes )

Let us factorise

Answer :

Given, f(y)= 2y3 – 5y2 –19y+ 42

In f(y) putting y=±1, ±2, ±3, we see for which value of y, f(y)=0


We observe that f(2) = 0

From factor theorem, we can say, (y−2) is a factor of f(y)

2y3 – 5y2 –19y+ 42= 2y3 – 5y2 –19y+ 42

= 2y3−4y2−y2+2y−21y+42

= 2y2(y−2)−y(y−2)−21(y−2)

= (y−2)(2y2−y−21)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses